Education and Library: A Symbiotic Approach for Sustainable Development in Nigeria - O.M. Audu, Ozohu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
While education is the knowledge acquire, which makes citizens part and parcel of the productive capacity of the society, there is no doubt that library is a major force in the educational sector as it serves as the foundation of quality educational system in a given society. This paper examined the possible outcome of the symbiotic relations between library and education in the developing world with particular reference to Nigerian society. From the available secondary data, the paper contends that library as a social institution plays a significant role in providing access to information materials to ensure quality education towards achieving sustainable development. The centre argument of the study is that library serves as a catalyst to sustainable development as outlined in MDGs and SDGs policies and programme especially in an emerging nation. Situating this within the Nigerian geopolitical space, the paper outlined some challenges confronting library and library management in the country. These challenges include; lack of fund and political will for the management of libraries, inadequate infrastructural facilities, and inadequate qualified personnel in Nigerian libraries among other. The paper concludes that should these challenges given favourable consideration, libraries in Nigeria and elsewhere will fast-track the attainment of sustainable development in the society. The study utilizes a historical methodology and the analytical approach was adopted.